Metadisciplinary strategy in students’ ecological competence forming - Elena N. Chekanushkina; Elena N. Ryabinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Pollution and environmental degradation affect the health and well-being of people. Modern society needs new mentality and the realization of the ideas of sustainable ecological development. The increasing role of the environmental education quality and upbringing of young people is of great importance. The formation and development of students’ environmental competence is also significant as it is a metadisciplinary concept and suggests acquiring common educational activities aimed at mastering the basic educational programs, realizing the internal potential and producing an educational result for solving complex professional problems, increasing efficiency own professional activity and importance for others. The analysis of the regulatory framework is conducted. These documents reflect the priorities and objectives of the state policy in the field of environmental development, education, culture and environmental sustainability. A modified model of the informational-didactic base system of students’ ecological preparation of humanitarian branches is proposed. It represents the subject-oriented interdisciplinary integration of the content of two or more academic disciplines. Integration is an immanently connected process of combining one of the learning elements of the discipline module with a certain element of the information-didactic ecological base. As a result of substantive-methodological integration, interdisciplinary didactic complexes of disciplines were created, linked together for the purpose of continuity, logical study of the material and the formation of students’ ecological competence. The interdisciplinary approach to the organization of the educational process takes into account the principles of continuity, regionality, sustainable development of the environment and society, universality. Practical implementation in the educational process of interdisciplinary didactic complexes of disciplines demonstrates the effectiveness of forming and developing students' meta-subject ecological competence.